Plugging the skills gap: the vital role that women should play in cyber-security. Issue 1 (January 2018) - Cobb, Michelle Johnson
Abstract : The past year has been dominated by cyber-security incidents in the news, including three of the biggest ransomware attacks ever to hit companies globally. Last September's massive Equifax breach continues to throw a spotlight on cyber-security and highlight how important it is for organisations to have protective cyber-security measures in place. Prior to the Apache Struts exploit, many organisations – including critical infrastructure firms – fell victim to WannaCry and NotPetya, increasing cyber-security concerns for nation states as well as businesses. While headlines are full of high-profile breaches, organisations are struggling to find enough people with cyber-security skills. Yet women remain notable by their absence in the cyber-security world. This isn't due to lack of qualifications. There are plenty of women with backgrounds in computer science and other technical and scientific fields who could meet this need. So why isn't this happening? Michelle Johnson Cobb of Skybox Security examines the hurdles that women face and, importantly, how they represent an untapped resource that could address serious issues faced by organisations.